2020
DOI: 10.1016/j.chom.2019.11.012
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella Secreted Effector SarA/SteE Mimics Cytokine Receptor Signaling to Activate STAT3

Abstract: Highlights d The bacterial effector SarA shares sequence and function with gp130 cytokine co-receptor d Phosphorylation of SarA's YxxQ motif facilitates direct binding to STAT3 d SarA-driven STAT3 activation requires interaction with active GSK-3 d SarA has greater affinity for STAT3 than gp130 and lacks the SOCS3 interaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…These results show that GSK3 is a central regulator of the balanced host response during infection, and that targeting GSK3 function is likely to make the host susceptible to disease. In line with this prediction, GSK3 was recently found to be co-opted by the Salmonella enterica serovar Typhimurium effector SteE to skew infected macrophage polarization and allow infection to persist(65,66). Our results suggest another possible effect of targeting GSK3 may be the inefficient upregulation of MHCII on Salmonella-infected macrophages in response to IFNg.…”
supporting
confidence: 83%
“…These results show that GSK3 is a central regulator of the balanced host response during infection, and that targeting GSK3 function is likely to make the host susceptible to disease. In line with this prediction, GSK3 was recently found to be co-opted by the Salmonella enterica serovar Typhimurium effector SteE to skew infected macrophage polarization and allow infection to persist(65,66). Our results suggest another possible effect of targeting GSK3 may be the inefficient upregulation of MHCII on Salmonella-infected macrophages in response to IFNg.…”
supporting
confidence: 83%
“…JAK phosphorylation of STAT3 and STAT6 on key tyrosine residues leads to nuclear translocation and activation of downstream targets responsible for M2 polarization. In keeping with this, Panagi et al (2020) and Gibbs et al (2020) found that STAT3 (but not STAT6) was phosphorylated on its key activating tyrosine residue, Y705, in a SteE-dependent manner, but that this was independent of JAK kinases. Immunoprecipitated (IP) SteE-GFP was sufficient to phosphorylate STAT3, suggesting that SteE either acts as a cryptic kinase (which would be surprising given its small size and lack of obvious domains),or that SteE is associated with another kinase responsible for this activity (Panagi et al, 2020).…”
mentioning
confidence: 64%
“…Three papers in this issue of Cell Host & Microbe now build upon these earlier findings to reveal a unique and unexpected mechanism by which SteE/SarA co-opts macrophage signaling to induce M2 polarization (Panagi et al, 2020;Gibbs et al, 2020) and demonstrate that this SteE/ SarA-mediated program counteracts a TNF-induced switch to microbicidal M1 macrophages, thus promoting Salmonella persistence within tissue granulomas (Pham et al, 2020).…”
mentioning
confidence: 87%
See 2 more Smart Citations